2007
DOI: 10.1136/oem.2006.031203
|View full text |Cite
|
Sign up to set email alerts
|

Occupational risk factors for asthma among nurses and related healthcare professionals in an international study

Abstract: Objective:The authors examined the relations between self-reported work tasks, use of cleaning products and latex glove use with new-onset asthma among nurses and other healthcare workers in the European Community Respiratory Health Survey (ECRHS II).Methods:In a random population sample of adults from 22 European sites, 332 participants reported working in nursing and other related healthcare jobs during the nine-year ECRHS II follow-up period and responded to a supplemental questionnaire about their principa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
130
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(151 citation statements)
references
References 25 publications
18
130
0
3
Order By: Relevance
“…Our results are consistent with a deleterious effect in the use of cleaning sprays on asthma phenotypes and with previous results on household exposure [6], from nurse cohorts [5] and cleaners in offices or private homes [1]. The lack of association between home cleaning, evaluated both by self-report and by PCA, and asthma phenotypes, is an argument in favour of the specific effect of products in spray form.…”
Section: Domestic Use Of Sprays and Asthma In Femalessupporting
confidence: 81%
See 1 more Smart Citation
“…Our results are consistent with a deleterious effect in the use of cleaning sprays on asthma phenotypes and with previous results on household exposure [6], from nurse cohorts [5] and cleaners in offices or private homes [1]. The lack of association between home cleaning, evaluated both by self-report and by PCA, and asthma phenotypes, is an argument in favour of the specific effect of products in spray form.…”
Section: Domestic Use Of Sprays and Asthma In Femalessupporting
confidence: 81%
“…BELLO et al [4], who studied detailed tasks among hospital cleaners, classified the use of cleaning sprays as high risk for inhalation exposure. The use of cleaning products in spray form, at work and at home, may be an important risk factor for asthma [1,5,6]. One study has reported a dose-response relationship between the frequency of use and number of cleaning sprays used at home and asthma incidence [6].…”
mentioning
confidence: 99%
“…The most persuasive evidence for chronic IIA related to chronic moderate irritant exposure asthma is provided by the epidemiologic studies of workers exposed to cleaning agents (47). The frequent use of bleach (hypochlorite), ammonia, and degreasing sprays has been consistently associated with asthma among workers exposed to cleaning agents (42,44,48), although the precise chemical exposures and the mechanisms responsible for the increased incidence of asthma have not been clarified since cleaning materials typically contain a wide variety of ingredients, some of which are respiratory irritants, while others are potential airway sensitizers (Table 6). Other occupations associated with increased risk of asthma that cannot be readily or completely explained on the basis of a clear sensitizing exposure are presented in Table 6 (47,(49)(50)(51)(52)(53)(54)(55)(56).…”
Section: Epidemiological Evidence For Irritant-induced Asthmamentioning
confidence: 99%
“…formaldehyde and isopropylic alcohol) can also be found in many indoor environments. These irritants are recognized as a possible cause of asthma [19][20][21]. Very few cases of IVCD have been described so far [16,22].…”
Section: Discussionmentioning
confidence: 99%